Perlindungan Investor Obligasi Di Pasar Modal Melalui Pendekatan Etika Bisnis Bagi Penerbit Obligasi - Sili, Eduardus Bayo (Jurnal Hukum & Pembangunan, 2016)
The success of a company in the business law perspective, it is not enough only measured by financial results and increase shareholder value (share holders value) merely, but people began to associate to how well the company has been applying the principles of good corporate governance. One of the forms of this principle of good corporate governance is the application of business ethics. Consistency of application of business ethics in the form of good corporate governance for the issuer (issuer) in managing the company, will no longer be just a merely appeal, but has become an ethical duty to be obeyed